1998
DOI: 10.1093/jac/41.3.329
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial prophylaxis in orthopaedic surgery: the role of teicoplanin

Abstract: Orthopaedic joint replacement is generally considered 'clean' surgery characterized by a low incidence of infection. In recent years the use of a clean theatre environment, high local concentrations of antibiotic in the cement and systemic antibiotic prophylaxis have been recognized as important measures to reduce infection rates significantly, and this has been supported by clinical trials. Staphylococcus aureus and Staphylococcus epidermidis cause at least half of all orthopaedic surgical infections. Gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…Therefore, the use of antibiotics is controversial, as inappropriate antibiotic prescribing with the increasing number of antibiotic-resistant strains further decreases its effectiveness [10]. In the controversy involving glycopeptides for prophylaxis, most authors agree that their use should be restricted [6,9,20] due to the increasing prevalence of vancomycin intermediately-resistant S. aureus (VISA) and vancomycin-resistant enterococci (VRE) [2] in the USA and Japan, in turn related to vancomycin overuse [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of antibiotics is controversial, as inappropriate antibiotic prescribing with the increasing number of antibiotic-resistant strains further decreases its effectiveness [10]. In the controversy involving glycopeptides for prophylaxis, most authors agree that their use should be restricted [6,9,20] due to the increasing prevalence of vancomycin intermediately-resistant S. aureus (VISA) and vancomycin-resistant enterococci (VRE) [2] in the USA and Japan, in turn related to vancomycin overuse [6].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, other authors [20] reviewing four available comparative trials of the efficacy and safety of teicoplanin in orthopaedic surgery prophylaxis conclude that teicoplanin 400 mg pre-operatively may be a reasonable choice for use in orthopaedic surgery when there is a high risk of infection with MRSA. Teicoplanin is tolerated better than vancomycin and is comparable to the cephalosporins [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the glycopeptide arms, infections due to MRSA were less frequent and were balanced by an increase in the incidence of infections due to methicillin-susceptible S. aureus (MSSA) (4,7). In addition, prophylaxis with glycopeptides has been associated with a higher rate of infection due to Gram-negative bacilli (8).…”
mentioning
confidence: 99%
“…Lower levels are achieved in fat (9,31). Finally, in four comparative trials on prosthetic joint implant surgery, single-dose teicoplanin was found to have efficacy and safety equivalent to those of multiple-dose cephalosporin (cefazolin, cefamandole, or cefuroxime) regimens (26).…”
mentioning
confidence: 99%
“…However, as most infections in joint prostheses are caused by staphylococci, the most widely used antibiotics are some cephalosporins and semisynthetic penicillins, by virtue of their excellent activity against the pathogens involved and their favorable pharmacokinetics and safety (7,21,22,24). The preferred agents seem to be cefazolin and cefamandole (26), and multiple doses of cefazolin are presently considered by most authors to be the standard prophylaxis in clean surgical procedures, including elective orthopedic surgery (2,3,8,15,20,23). However, methicillin-resistant (MR) coagulasepositive and -negative staphylococci are increasingly being reported as nosocomial pathogens, therefore suggesting the use of antimicrobial agents effective against these MR microorganisms in the prophylaxis for prosthetic orthopedic surgery, particularly in hospitals in which there is high resistance among these nosocomial pathogens (11,12).…”
mentioning
confidence: 99%